Action of the diaphragm on the rib cage - Troyer, André De; Wilson, Theodore A. (Journal of applied physiology (1985), 2016)
When the diaphragm contracts, pleural pressure falls, exerting a caudal and inward force on the entire rib cage. However, the diaphragm also exerts forces in the cranial and outward direction on the lower ribs. One of these forces, the “insertional force,” is applied by the muscle at its attachments to the lower ribs. The second, the “appositional force,” is due to the transmission of abdominal pressure to the lower rib cage in the zone of apposition. In the control condition at functional residual capacity, the effects of these two forces on the lower ribs are nearly equal and outweigh the effect of pleural pressure, whereas for the upper ribs, the effect of pleural pressure is greater. The balance between these effects, however, may be altered. When the abdomen is given a mechanical support, the insertional and appositional forces are increased, so that the muscle produces a larger expansion of the lower rib cage and, with it, a smaller retraction of the upper rib cage. In contrast, at higher lung volumes the zone of apposition is decreased, and pleural pressure is the dominant force on the lower ribs as well. Consequently, although the force exerted by the diaphragm on these ribs remains inspiratory, rib displacement is reversed into a caudal-inward displacement. This mechanism likely explains the inspiratory retraction of the lateral walls of the lower rib cage observed in many subjects with chronic obstructive pulmonary disease (Hoover's sign). These observations support the use of a three-compartment, rather than a two-compartment, model to describe chest wall mechanics.